The Impact of Training, Knowledge Management, and Discipline on Employee Effectiveness, with the Work Environment as A Moderating Variable at the Ministry of Health of the Republic of Indonesia - Riki Arli; Dewi Susita; Despinur Dara (Indonesian Journal of Multidisciplinary Science, 2026)
Employee effectiveness is a critical factor in supporting the achievement of organizational goals, particularly in public sector institutions such as the Ministry of Health of the Republic of Indonesia, which faces increasing demands arising from digital transformation and complex public service challenges. This study aims to examine the effects of training, knowledge management, and work discipline on employee effectiveness, as well as the moderating role of the work environment in these relationships. This research employed a quantitative approach using an explanatory research design. Data were collected through questionnaires distributed to employees of the Ministry of Health of the Republic of Indonesia, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that training, knowledge management, and work discipline have positive and significant effects on employee effectiveness. Training was identified as the strongest factor contributing to employee effectiveness, followed by knowledge management and work discipline. Furthermore, the work environment significantly moderated the relationships between training, knowledge management, and work discipline and employee effectiveness, indicating that a supportive work environment strengthens the influence of these factors. The findings highlight that improving employee effectiveness requires not only individual competency development but also organizational support through effective knowledge management, discipline reinforcement, and the creation of a conducive workplace environment. This study provides practical implications for the Ministry of Health in developing sustainable human resource management strategies to enhance employee effectiveness and organizational performance.